Indole Alkaloids from Aspidosperma rigidum and A. schultesii and their Antiparasitic Effects - Reina, M (2011)
This work was supported by grant CTQ2009-14629-C02-01 (Spain) and the Collaborative Research Project CSIC-CONCYTEC (Peru). W. R. M. thanks MAE-AECI (Spain) for a predoctoral fellowship. We also thank S. Carlin for language advice.